The Ottoman Economy (1870-1913): Preliminary Second-Generation Estimates - Mehmet Bulut; Bora Altay (Türkiye İslam İktisadı Dergisi)
The purpose of this study is to present a new estimate on the GDP and per capita GDP levels of the Ottoman Empire between 1870 and 1913. Since the earlier estimates employ different methods, this study re-combines data series using reliable secondary sources while attempting to incorporate the distribution margins, includes industrial production excluded from the industrial census, and correcting missing information in certain agricultural productions. The inclusion of “Distribution Margins” (DMs) that adjust from producer to market prices reflects the price difference which entails diverse GDP and per capita GDP levels. The DMs are crucial, especially to incorporating costs of distributing industrial and agricultural products between the center and periphery. This research concludes that GDP and per capita GDP levels were higher than those made by earlier estimates. The method and findings of this study make contributions to the recent discussions on the economic performance of the Ottoman Empire, particularly for the period preceding the First World War. This study also suggests new research areas to further improve future studies on GDP and per capita GDP levels of the Ottoman Empire.